Development of the Tendency to Use Emotion Regulation Strategies and Their Relation to Depressive Symptoms in Chinese Adolescents - Sai, Liyang; Luo, Sichen; Ward, Anne; Sang, Biao (Frontiers in Psychology, 2016)
The present study examined the development of the tendency to use cognitive reappraisal/expressive suppression in daily life and how they relate to depression in Chinese adolescents. Results showed that Chinese adolescents reported using less expressive suppression as age increased, while there was no age effect for the tendency to use cognitive reappraisal. Further, linear regression analysis revealed that the tendency to use cognitive reappraisal in daily life negatively predicted depressive symptoms, while the tendency to use expressive suppression in daily life positively predicted depressive symptoms. These findings provide evidence that support the development of emotion regulation strategies in childhood and adolescence.